ANALISIS KESALAHAN PENGGUNAAN KATA GANTI ORANG DALAM KARANGAN NARASI SISWA KELAS VII SMPN 31 MAKASSAR - Nursamsilis Lutfin (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2021)
This study aims to determine the application of personal pronouns in narrative essays for class VII C students of SMPN 31 Makassar. The method used in this research is descriptive qualitative method. In this study the researcher did not give any treatment to students as a data source. As for the subjects of the research were students of class VII.C. This research was obtained through a purposive sampling technique. The number of students taken as a sample is 10 people. This research instrument was assisted by observation tables to record data in the form of sentences contained in drama writing using appropriate or inappropriate personal pronouns in their application and use. In collecting data, the researcher started by giving assignments in the form of writing drama scripts and reading the scripts. After that the researcher classifies the data based on the task given. Based on the results of research on errors in the use of personal pronouns in narrative essays for class VIII.C even semester students of SMPN 31 Makassar, it can be concluded that of all the narrative essays analyzed, it can be said that the pronoun that appears the most is the first-person pronoun which shows meaning plural (kami dan kita). The second order is third person pronouns that show a singular meaning (-nya, dia, dan ia) followed by first person pronouns that show a singular meaning (saya, aku, dan -ku), second person pronouns that show a singular meaning (-mu, kamu, dan -kau), third person pronouns that show a plural meaning (mereka). The pronoun that appears the least in the students' narrative essays is the second person pronoun which shows a plural meaning (kalian).